The edges of the world (India, Indian Ocean, Eastern and Southern Africa) in the so-called Jerome maps : an investigation into their toponymy - (:unkn) unknown (My University, 2021)
This chapter will be part of a book devoted to the so-called « Jerome » maps (map of Asia ; map of the Holy Land) which P. Gautier Dalché, St. Lebreton and P. Schneider are co-editing. The toponymy of the two maps will be studied in a specific chapter, with particular attention to the relationship between medieval toponyms and ancient geography. The section written by P. Schneider deals with Eastern Asia, Eastern and southern Africa and the Erythraean Sea area. This text is a pre-print version.
Keywords: African Research